THE EDUCATIONAL POINT OF THE “NUSSA THE MOVIE” ANIMATION MOVIE PRODUCTION BY BONY WIRASMONO - Nidia Sulistyowati; Syalwa Bella Sopian; Irma Rasita Gloria Barus; Ira Resmayasari (Jurnal Pendidikan dan Kebudayaan (JURDIKBUD), 2022)
The film " Nussa The Movie" is a breakthrough in the film with Islamic animation nuances with the plot presented easily for children to understand. The film is designed to invite children to be interested in manual or digital literacy, especially in Islamic activities. With a myriad of meanings, this story tells the story of the character of Nussa as the defending champion of the science fair with its limitations. The purpose of this paper is to examine and analyze literacy from the point of view of parents who have little time for their children, based on the results obtained through research on data sources and internet studies. Knowledge of the importance of literacy in children is decreasing due to the use of smartphones that are not wise and the attention of parents is not optimal. In conclusion, the development of literacy in children is less emphasized on letter knowledge and language use skills, among others; introduce vocabulary through objects, invite children to read books, train children to appreciate an object, and teach children about sincerity. This literacy learning mode uses a social and technological approach. The research results reveal that digital literacy is better able to increase awareness to build a mature mindset.